Estimasi Sistem Perlapisan pada Blok-A Area Panas Bumi Lainea Konawe Selatan Menggunakan Vertical Electrical Sounding (Ves) Konfigurasi Schlumberger - Syafira Mpuhu; Jamhir Safani; Syamsul Razak Haraty (Jurnal Rekayasa Geofisika Indonesia, 2025)
This research aims to estimate the layering system in the Lainea Geothermal area in South Konawe Regency. The apparent resistivity data obtained from the Pusat Sumber Daya Geologi (PSDG) measured in 2010 using the Schlumberger configuration was inversed with the particle swarm optimization (PSO) method. From the results of data inversion at both sounding points, it was found that there are five layers with different resistivity ranges. The first layer is a thin overburden near the surface with a thickness of 0.5 - 0.7m. The second layer is thought to be conglomerate rock. The third layer is interpreted as cap-rock with meta-sandstone lithology with a resistivity value range of 126.3<ρ<366 Ωm. The fourth layer with sandstone lithology is closely suspected as a fluid accumulation zone with a resistivity value range of 45.4<ρ<69 Ωm. The lowest layer with a resistivity value range of 261<ρ<500 Ωm is interpreted as metamorphic rock which is thought to act as an impermeable layer.